(3GdeSFhdjI GdeOfjI ddehQO Ydi THcGJ GdeYdheGJ (B/ s - (3GMeO ceGd GMeO UHQis; (3eMeO TcQi SQhQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3fJfGhd ai gPg GdQSGdI ehVhYGdeSFhdjI GdeOfjI ddehQO Ydi THcGJ GdeYdheGJhJQLY GgejI gPg GdOQGSI Gdi GfJTGQ GdGfJQfJ Ydi GdeSJhi GdOhdi hGdhWfi aCUHM jSjWQ Ydi cd MjGJfG (B: (3aGdeSJNOe jSJWjY GdONhd Gdi Jdc GdTHcI hGdMUhd Ydi GdeYdheGJ HSghdI hjSQ (B: (3hYdi GdLGfH GdGNQ fLO GdehQO GdPi jbhe HfTQ Jdc GdeYdheGJ hGVYG ai GYJHGQg JMbjb GdQHMagPg GdOQGSI aQUI dHMK cjajI fTQ GdeYdheI Ydi GdTHcI heGgjI fXGe GdeSFhdjI GdeJQJHI Ydi gPG GdfTGW (B: (3hfXQG dMOGKI gPG GdfTGW aGf GdOQGSI JbJVi GdJYQV ddMdhd GdbVGFjI GdJi GfJgi GdjgG GdbVGA ai GdMGdGJ GdeYQhVI Ydjgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi (B2006s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B618-650s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdGfJQfJs; (3GdehQOs; (3THcGJ GdeYdheGJs; (3eLJeY GdeYdheGJjI s; (3GdGJUGdGJ Yf HYOs; (3GddLfI GdbhejI ddeYdheGJjI hGdMQjGJ s; (3GdGdJRGe HGdEYdGe s; (3MeGjI GdeUfaGJ s; (3JCejf GdeYdheGJ s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs